Low cost control and monitoring motion control ICs - Moutinho, J. (2006)
For a long time, controlling AC motors in an efficient way, was a task only in the reach of some very specific electronic design Engineers. Now, with the up rise of Integrated Platforms it is possible to implement, with almost no effort, the desired application, customizing almost everything at the reach of a simple and user friendly software interface. However, the simplicity in control and monitoring has a major settle back. As expected, such products, very desirable by the market, are only sold in conjunction with an evaluation platform. Sometimes this platform does not fit the consumer needs and buying the full package is not a satisfactory solution, especially if it is just to get the control and monitoring software. In this paper, it will be show that low cost alternatives are possible. Using free tools and manufacturer’s documentation, it is simple to implement Motor Control with the desired IC by means of a very intuitive and complete Graphical Unit Interface (GUI), built attending our special needs.